2016
DOI: 10.24198/pjd.vol28no2.13723
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of temporomandibular disorder based on RDC/TMD Axis I revision 2010 in dentistry students

Abstract: Introduction: Temporomandibular joint disorders is a pathologic conditions as a caused of musculoskeletal pain and dysfunction syndrome in stomatognathic system. This disorder was suffered in the population and affected the quality of life. This study was done to know how was the condition of temporomandibular joint disorders in the student of Faculty of Dentistry Universitas Padjadjaran population. Another objective of this study was the diagnosis classification of revised RDC-TMD Axis I could be applicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
1
0
6
Order By: Relevance
“…The female predominance of TMJ disorders may be associated with the sex hormone oestrogen, as its receptors could change metabolic function, increasing ligament weakness and pain stimulation by modulating the limbic system. 14 15 16 A statistical analysis of symptoms showed that women reported more frequent complaints of pain in the temporomandibular joint, facial muscles, neck and shoulder area, headaches, fatigue in masticatory muscles, and sensitive teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The female predominance of TMJ disorders may be associated with the sex hormone oestrogen, as its receptors could change metabolic function, increasing ligament weakness and pain stimulation by modulating the limbic system. 14 15 16 A statistical analysis of symptoms showed that women reported more frequent complaints of pain in the temporomandibular joint, facial muscles, neck and shoulder area, headaches, fatigue in masticatory muscles, and sensitive teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Tidak adanya osteoarthritis berhubungan dengan rentang usia responden. Osteoarthritis biasanya diderita oleh pasien dengan rentang usia 55-56 tahun 27 .…”
Section: Andalas Dental Journalunclassified
“…Jika stres bersifat kronik dan berkelanjutan, maka dapat mengganggu fungsi normal dalam sebuah sistem termasuk pada sistem mastikasi . Di Indonesia, sekitar 50% mahasiswa setidaknya memiliki satu diagnosis TMD dan yang paling banyak adalah dislokasi diskus dengan reduksi baik pada satu sendi atau keduanya yang diikuti oleh nyeri miofasial dengan keterbatasan bukaan rahang 16 .…”
Section: Hubungan Stres Dengan Temporomandibular Disorder Pada Mahasiswa Fakultas Kedokteran Gigi Universitas Andalasunclassified